The Relationship Between Motivation and Interest of Village Youth to Work in the Agricultural Sector in Paguyaman District, Boalemo Regency - Ibrahim, Winarti; Djibran, Moh. Muchlis; Indriant, Merita Ayu; Gobel, Yusriyah Atikah (International Journal Papier Advance and Scientific Review, 2020)
Motivation is a drive that comes from within and from outside that can affect youth to work in the agricultural sector. This research was conducted in Paguyaman District. The purpose of this study was to determine the relationship between motivation and the interest of village youth to work in the agricultural sector. Analysis of the data used is relationship analysis (Chi-Square). The results showed that there was no relationship between motivation and interests of youth with a value of x2 count (4.779) smaller than the value of x2 table (9.487), so it can be concluded that H1 is rejected and H0 is accepted